ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT/INTENSI KEWIRAUSAHAAN MAHASISWA - Tamriatin Hidayah (STIE Mandala Jember, 2012)
The reseach was done on the influence of variable analisis Traits, subjective norm, and Self efficacy to entrepreneurial Intentions.This study aims to determine the influence of Traits, subjective norms and self-efficacy on entrepreneurial intentions. The sample used in this study were 100 students of Mandala Economy College in Jember. Methods of data collection by questionnaire is given directly to respondents. Analytical test equipment used in this study is to Regression analysis. It’s founded that, simultaneously there was a significant correlation among Traits, Subjective Norm, and Self Efficacy to entrepreneurial Intentions students of Mandala Economy College in Jember. Partially there wasa significant correlation among Traits and Self Efficacy to entrepreneurial Intentions students of Mandala Economy College in Jember, but there was no significant correlation among Subjective Norm to entrepreneurial Intentions students of Mandala Economy College in Jember.